Kontribusi Masyarakat Dalam Evaluasi Pengembangan Kurikulum Di Madrasah Ibtidaiyah - Maulida Khafidoh; Ikhlasul Amaliah (Tematik: Jurnal Pendidikan Dasar Islam, 2025)
This study aims to examine the contribution of the community in the evaluation of curriculum development at Madrasah Ibtidaiyah Cokroaminoto 02 Bondolharjo. The research background is based on the importance of community involvement to create a curriculum that is relevant to local needs, Islamic values, and the development of the times. This research uses a qualitative method with a descriptive approach and a type of field research. Data were obtained through observation, semi-structured interviews, and documentation, then analyzed using Miles and Huberman's interactive analysis model with source triangulation for data validity. The results show that community involvement, including religious leaders, parents, and local communities, contributes significantly to the formulation, implementation, and evaluation of the curriculum. These contributions include financial, academic, and cultural support, as well as active participation in annual curriculum development meetings. This participation not only increases the relevance and quality of learning but also builds positive reciprocal relationships between schools and communities. The research concludes that the active contribution of the community is a key element in creating a contextual, responsive, and meaningful curriculum for students.